Dosimetric comparison using different multileaf collimeters in intensity-modulated radiotherapy for upper thoracic esophageal cancer - Gong, Youling (BioMed Central, 2010)
PURPOSE: To study the impacts of multileaf collimators (MLC) width [standard MLC width of 10 mm (sMLC) and micro-MLC width of 4 mm (mMLC)] in the intensity-modulated radiotherapy (IMRT) planning for the upper thoracic esophageal cancer (UTEC). METHODS AND MATERIALS: 10 patients with UTEC were retrospectively planned with the sMLC and the mMLC. The monitor unites (MUs) and dose volume histogram-based parameters [conformity index (CI) and homogeneous index (HI)] were compared between the IMRT plans with sMLC and with mMLC. RESULTS: The IMRT plans with the mMLC were more efficient (average MUs: 703.1 ± 68.3) than plans with the sMLC (average MUs: 833.4 ± 73.8) (p < 0.05). Also, compared to plans with the sMLC, the plans with the mMLC showed advantages in dose coverage of the planning gross tumor volume (Pgtv) (CI 0.706 ± 0.056/HI 1.093 ± 0.021) and the planning target volume (PTV) (CI 0.707 ± 0.029/HI 1.315 ± 0.013) (p < 0.05). In addition, the significant dose sparing in the D(5 )(3260.3 ± 374.0 vs 3404.5 ± 374.4)/gEUD (1815.1 ± 281.7 vs 1849.2 ± 297.6) of the spinal cord, the V(10 )(33.2 ± 6.5 vs 34.0 ± 6.7), V(20 )(16.0 ± 4.6 vs 16.6 ± 4.7), MLD (866.2 ± 174.1 vs 887.9 ± 172.1) and gEUD (938.6 ± 175.2 vs 956.8 ± 171.0) of the lungs were observed in the plans with the mMLC, respectively (p < 0.05). CONCLUSIONS: Comparing to the sMLC, the mMLC not only demonstrated higher efficiencies and more optimal target coverage, but also considerably improved the dose sparing of OARs in the IMRT planning for UTEC.